THE The evaluation of epicardial adipose tissue and carotid intima-media thickness in patients with Behçet’s disease - Sağlam, Gonca; Turgut, Mehmet Cenk; Gülcü, Oktay (Vojnosanitetski pregled, 2022)
Background/Aim. Epidemiological studies indicate that cardiovascular disease (CVD) is common in almost all patients diagnosed with autoimmune disease. This study aimed to examine whether epicardial adipose tissue (EAT) thickness (EATT) and carotid intima-media (CIM) thickness (CIMT) differ between patients with Behçet’s disease (BD) and healthy individuals. Methods. A total of 40 healthy subjects as controls and 40 BD patients with musculoskeletal complaints were enrolled in this cross-sectional prospective study. Socio-demographic, clinical, and laboratory data were obtained and compared between groups. The Behçet’s Disease Current Activity Form was used to assess disease activity. Both groups underwent echocardiography in order to measure EATT and CIMT. Results. The mean thickness of EAT (5.70 ± 1.05 mm; 2.50 ± 0.61 mm, respectively, p < 0.001) and CIM (0.68 ± 0.05 mm; 0.63 ± 0.06 mm, respectively, p = 0.002) were significantly increased in BD patients compared to the control group. A positive correlation was observed between EATT and age (r = 0.500, p = 0.001), the duration of the disease (r = 0.330, p < 0.001), waist circumference (r = 0.316, p = 0.013), and disease activity (r = 0.31, p < 0.001) in the patient group. CIMT was positively correlated with age (r = 0.594, p = 0.001) and the duration of the disease (r = 0.585, p = 0.001). The use of glucocorticoids or clinical manifestations (joint involvements, genital ulcer, skin lesions, inflammatory back pain, and major organ involvement) of the patients were not found to be associated with EATT or CIMT. Conclusion. EATT and CIMT are increased in patients with BD and are associated with disease activity. Echocardiographic measurement of EATT and CIMT is an objective, noninvasive, and available method that can evaluate the risk of subclinical atherosclerosis in patients with BD.